The Role of Teaching Strategies in Social Acceptance and Interactions; Considering Students With Intellectual Disabilities in Inclusive Physical Education - Furrer, Vitus; Valkanover, Stefan; Eckhart, Michael; Nagel, Siegfried (Frontiers in Education, 2020)
Including students with intellectual disabilities in primary school-based physical education (PE) is common practice. However, little is known about students’ social participation in this environment and how it is related to PE teaching strategies. This multilevel study explored the relations between the teaching strategies teaching cooperative norms using individual reference norm orientation (IRNO), taking into consideration students’ social acceptance and interactions in inclusive PE. The results showed that IRNO is positively related to social acceptance and positive interactions in inclusive PE, and the special educational need (SEN) status of children with intellectual disabilities moderated both relationships. Hence, IRNO helps to decrease the gap in social integration between students with and without intellectual disabilities. Teaching cooperative norms were also positively related to social acceptance of all children in PE, but there was no cross-level interaction for SEN status, and no relationship with positive interactions in PE. Thus, teaching cooperative norms can be seen as an inclusive PE teaching strategy that foster social participation and the well-being of all students. This study addresses an issue relevant in many countries where inclusive school settings are prioritized. In future, research on social participation, teacher, student, and class characteristics should be acknowledged.